2012
DOI: 10.1007/s10295-011-1036-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced enzyme production with the pelleted form of D. squalens in laboratory bioreactors using added natural lignin inducer

Abstract: White-rot fungi are extensively used in various submerged biotechnology processes to produce ligninolytic enzymes. Transfer of the process from the laboratory to the industrial level requires optimization of the cultivation conditions on the laboratory scale. An interesting area of optimization is pellet growth since this morphological form solves problems such as the decreased oxygen concentration, limited heat, and nutrient transport, which usually occur in dispersed mycelium cultures. Many submerged ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…Under optimal mixing conditions, the STR has shown to promote and enhance the production of certain fungal enzymes. Babiĉ and Pavko [79] observed an increased production of laccase by pellets of the white-rot fungus, Dichomitus squalens, when cultivated under optimal conditions in a STR with a natural inducer (saw dust). The laccase production was higher than those obtained when incubated in a bubble column reactor.…”
Section: Stirred Tank Reactormentioning
confidence: 98%
“…Under optimal mixing conditions, the STR has shown to promote and enhance the production of certain fungal enzymes. Babiĉ and Pavko [79] observed an increased production of laccase by pellets of the white-rot fungus, Dichomitus squalens, when cultivated under optimal conditions in a STR with a natural inducer (saw dust). The laccase production was higher than those obtained when incubated in a bubble column reactor.…”
Section: Stirred Tank Reactormentioning
confidence: 98%
“…This result shows that the pellets were damaged by the mechanical forces created in stirred tank bioreactor. It is generally observed that the pellet size decreases with increasing agitation intensity, which is related to mechanical shear forces [20,21]. It was reported that higher shear forces created in stirred tank bioreactor can destroy the hairiness of the fungal pellets [22].…”
Section: Morphology and Biomass Growthmentioning
confidence: 99%
“…Smaller and less compact pellets were formed at the highest agitation rate of 300 rpm [20]. Mild agitation rates are preferable for laccase production by Dichomitus squalens and Pleurotus ostreatus in stirred tank bioreactors [21,23]. The laccase production by Panus tigrinus on olive mill wastewater-based media was influenced negatively when the stirrer speed was increased [35].…”
Section: Flavor Productionmentioning
confidence: 99%
See 2 more Smart Citations